Exploring Determinant Factors of Bond Trading with Inventory Management Theory (Case Study of Indonesian Capital Market, January – March 2009) - Wahyudi, Imam; Robbi, Abdu (The Indonesian Capital Market Review, 2010)
This paper studies trading volume of 206 recorded and publicly traded bonds in Indonesian Capital Market on January 4th - March 9th 2009 observed period. The data covers almost all trading data in the market and all brokers that exist. The microstructure data used in this study is a complete understanding for almost every phenomenons in the market, and thus could explain more about bond liquidity. We ind that some bonds are actively traded and most are rare. We also construct some determinant facto tests of bond trading volume, included descriptive statistic, GLS, and other formal test. We ind that bonds with larger par value and more seasoned tend to have smaller trading volume. We also ind that private bonds are actively traded more than public bonds (both government institution and private institution bond). Interest rate risk and bond price volatility are positively inluence bond trading volume, but opposite for bond rating. We ind that bond with higher probability to default have smaller trading volume. While comparing the bond volume data with stock price data, we ind that the relationship in two markets is not linier as the convenient theory in inance said.